Restorasi ekologi lahan gambut berbasis kelompok masyarakat mandiri melalui revegetasi di Desa Tanjung Leban Kabupaten Bengkalis, Riau - Almasdi Syahza; Osamu Kozan; Sigit Sutikno; Mitri Irianti; Kei Mizuno; Michiko Hosobuchi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Ecological restoration of peatlands leads to the destruction of peatland ecosystems caused by human activities, whether intentional or not. As a result of the damage caused various kinds of problems such as land fires. Tanjung Leban Village is one of the villages with a fairly high rate of fire, especially in 2012, 2013, and 2015. Many burnt lands are left unused, which in turn becomes a fire-prone area due to the lack of control over the land. In response to this, it is necessary to carry out peatland ecological restoration activities in Tanjung Leban Village through revegetation activities. Implementation of activities with the mentoring method through village facilitators stationed in Tanjung Leban Village. The implementation process begins with socialization, which continues with group formation, procurement of seeds, land clearing, and planting. The implementation of this revegetation focuses on the participation of the community who are members of the Peat Care Community Group (MPG) in Tanjung Leban Village. This activity was carried out in the community area (group members) with an area of 14.7 ha and 14,381 plants. The number of plants is divided into 2 categories, namely natural wood species and fruit plants.